Пошаговое объяснение:
1 число = х + 52
2 число = х
3 число = 1/3 * х = 1/3х
х + 52 + х + 1/3х = 24,6
2. 1/3х + 52 = 24,6
2. 1/3х = 24,6 - 52
7/3х = -27,4
7/3х = -27. 4/10
7/3х = -274/10
х = -274/10 : 7/3
х = -274/10 * 3/7
х = -137/5 * 3/7
х = -411/35
х = -11. 26/35
1 число = (х + 52) = -11. 26/35 + 52 = -11. 26/35 + 51. 35/35 = 40. 9/35
2 число = (х) = -11. 26/35
3 число = (1/3х) = 1/3 * (-11. 26/35) = 1/3 * (-411/35) = 1/1 * (-137/35) = -137/35 =
-3. 32/35
Проверка:
40. 9/35 + (-11. 26/35) +
(-3. 32/35) =
40. 9/35 - 11. 26/35 - 3. 32/35 =
39. 44/35 - 11. 26/35 -
3. 32/35 =
28. 18/35 - 3. 32/35 =
27. 53/35 - 3. 32/35 =
24. 21/35 = 24. 3/5 = 24,6
Пошаговое объяснение:
1 число = х + 52
2 число = х
3 число = 1/3 * х = 1/3х
х + 52 + х + 1/3х = 24,6
2. 1/3х + 52 = 24,6
2. 1/3х = 24,6 - 52
7/3х = -27,4
7/3х = -27. 4/10
7/3х = -274/10
х = -274/10 : 7/3
х = -274/10 * 3/7
х = -137/5 * 3/7
х = -411/35
х = -11. 26/35
1 число = (х + 52) = -11. 26/35 + 52 = -11. 26/35 + 51. 35/35 = 40. 9/35
2 число = (х) = -11. 26/35
3 число = (1/3х) = 1/3 * (-11. 26/35) = 1/3 * (-411/35) = 1/1 * (-137/35) = -137/35 =
-3. 32/35
Проверка:
40. 9/35 + (-11. 26/35) +
(-3. 32/35) =
40. 9/35 - 11. 26/35 - 3. 32/35 =
39. 44/35 - 11. 26/35 -
3. 32/35 =
28. 18/35 - 3. 32/35 =
27. 53/35 - 3. 32/35 =
24. 21/35 = 24. 3/5 = 24,6